"Baseball Is Whack!": Exploring the Lack of African American Baseball Consumption. (August 2015) - Brown, Brandon; Bennett, Gregg
The purpose of this study is to assess the African American viewpoint on baseball consumption. Utilizing a criterion purposive sample of African Americans, the authors used a qualitative analysis to obtain viewpoints that provide a rich understanding of the motivations to consume (or not consume) baseball. Likewise, the authors investigated the facets of baseball that seemingly create social and psychological consumption barriers for African Americans. The findings suggest three broad categories best represent the deterrence from baseball consumption: attitudes toward baseball consumption, social constraints related to consuming baseball, and the role of racial identification toward sport consumption. Within these three categories, seven general dimensions evolved that, if present, would thus influence perceptions toward baseball and eventually affect consumption habits.